Comparative evaluation of the effect of four commonly used toothpaste brands in Iran on enamel abrasion - Jaber Yaghini; Ahmad Moghareh Abed; Maedeh Kaveh; Mohammad Sadegh Alem-Rajabi (Isfahan University of Medical Sciences, 2011)
Introduction: Tooth brushing with a toothpaste is the most frequent and important method to maintain oral hygiene. However, using such products has its side effects, including tooth abrasion. The aim of this study was to compare abrasiveness of aforeign whitening toothpaste and three similar Iranian brands. Materials and Methods: In this in vitro experimental study four groups of enamel samples, each consisting of 6 samples, were prepared and embedded in acrylic blocks. The samples were 5×5×5 mm and were prepared from 24 sound extracted human anterior teeth. The initial surface profile for each specimen was calculated using a profilometer. The samples underwent a wear test in a V8 Cross Brushing machine using toothbrushes and a toothpaste solution. The samples were then dried and the surface profile was again calculated. The difference between the first and second profilometer calculations demonstrated wear for each specimen. Data was analyzed using the SPSS program by means of one-way ANOVA and repeated measures ANOVA (α=0.05).Results: According to repeated measures ANOVA, there were significant differences between means of profilometry before and after of abrasion (p value < 0.0001). However, this effect was not significant for toothpaste type (p value = 0.991). One-way ANOVA did not reveal any significant differences between means of differences before and after abrasion among the four groups.Conclusion: According to the results there were no significant differences between enamel abrasion by Iranian toothpastes and a foreign one. Key words: Abrasive, Profilometry, Tooth enamel, Toothpaste.